Hate Crime Pasca Pemilihan Umum Presiden Tahun 2024 Di Indonesia - Novarizal, Riky; Siregar, Rahmat Amin; Shiddiqy, Muhammad Arsy Ash (UIR Press, 2025)
Presidential elections are often accompanied by various phenomena, including hate crimes that persist even after the elections have concluded. This phenomenon has not yet been thoroughly studied through social media analysis. In response to the gaps in previous research, this study focuses on sentiment analysis on social media, the forms of hate crime, and their contributing factors. The study presents three key findings related to hate crimes following the 2024 presidential election in Indonesia. First, Ganjar Pranowo received the least negative sentiment, followed by Anies Baswedan and Prabowo Subianto. Second, hate crimes directed at presidential candidates took the form of ethnic-based sentiment, anti-religion hatred, and threats of violence. Third, factors influencing the emergence of hate crimes post-election include the influence of social media popularity, sponsorship by electoral actors, weak enforcement of campaign violations, and the history of political and ethno communal violence. The study also emphasizes the need for future research to examine post-election hate crimes by integrating multidisciplinary approaches on social media. This would enrich the data and provide more comprehensive knowledge about hate crime phenomena and other forms of digital crime arising from the electoral process.